2019
DOI: 10.1021/acs.jpca.9b00327
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional H Atom Tunneling Dynamics of Phenol: Interplay between Vibrations and Tunneling

Abstract: Multidimensional facets of the hydrogen tunneling dynamics of phenol excited in S1 (ππ*) have been unraveled to give particular S1 vibronic states strongly coupled or actively decoupled to the O–H tunneling coordinate. Strong mode-dependent variation of the tunneling rate measured with picosecond lasers indicates that tunneling probability is extremely sensitive to low-frequency vibrational modes seemingly orthogonal to the O–H elongation coordinate unless the rate of energy randomization exceeds that of tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 47 publications
(110 reference statements)
1
51
0
Order By: Relevance
“…By measuring both the ps transients of parent and fragment and the total translational energy distribution of products as a function of the reaction time, it was evidenced that both the slow and fast components of the H fragment have the same tunneling origin and that the ground state is populated at the second ps*-S 0 crossing and not through a direct pp*-S 0 internal conversion process. 24,37 The H-loss dynamics have also been studied in the time domain. The ps time-evolution of the S 1 excited state of PhOH shows that the lifetime decreases from 2 ns at the band origin 0 0 0 down to 600 ps at the band located 3500 cm À1 above the origin.…”
Section: The Sddj Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…By measuring both the ps transients of parent and fragment and the total translational energy distribution of products as a function of the reaction time, it was evidenced that both the slow and fast components of the H fragment have the same tunneling origin and that the ground state is populated at the second ps*-S 0 crossing and not through a direct pp*-S 0 internal conversion process. 24,37 The H-loss dynamics have also been studied in the time domain. The ps time-evolution of the S 1 excited state of PhOH shows that the lifetime decreases from 2 ns at the band origin 0 0 0 down to 600 ps at the band located 3500 cm À1 above the origin.…”
Section: The Sddj Modelmentioning
confidence: 99%
“…15 This model was ultimately dismissed following the demonstration of the correlation of the excited state lifetime of PhOH and its derivatives with the pp*/ps* gap. 24,34,37 It should be stressed that the cNH 4 (NH 3 ) n clusters can be seen as a very good messenger for characterizing the H loss on a ps* potential. Indeed, the H transfer requires a fairly direct process (the dynamics occur on a repulsive surface) since a process going through hot ground state molecules (H loss mediated by internal conversion to the ground state 33 ) would lead to a statistical process (Intramolecular Vibrational Redistribution: IVR) and the immediate evaporation of the whole cluster or some of the NH 3 molecules.…”
Section: The Sddj Modelmentioning
confidence: 99%
“…By measuring both the picosecond transients of parent and fragment and the total translational energy distribution of products as a function of the reaction time, it was evidenced that both the slow and fast components of the H fragment have the same tunneling origin and that the ground state is populated at the second *-S0 crossing and not through a direct *-S0 IC process. 54 Using picosecond laser, a complete survey of the evolution of the excited lifetime of phenol as a function of the excess energy has shown that the lifetime changes from 2 ns at the band origin 00 0 to 600 ps at 3500 cm -1 above. 54,55 These surveys show that the excitation of A" symmetry vibrational levels in the S1 state shortens the lifetime, mainly through S1-S2 vibronic coupling.…”
Section: Phenol Chromophorementioning
confidence: 99%
“…It is theorized that the photostability of tyrosine arises, in part, from the availability of an excited state relaxation channel in the phenol moiety wherein O-H bond extension facilitates non-radiative decay back to the ground state. [1][2][3][4] This bond extension and complete O-H bond fission in such molecules has thus been the subject of extensive study, both experimentally [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and computationally. 1,[22][23][24][25][26][27][28][29][30][31][32][33] Experimental studies have shown that the photodissociation of phenol following excitation at wavelengths  ~270 nm proceeds via excitation from the ground electronic state, S0, to the first excited singlet state, S1, which has 1 ππ* character in the Franck-Condon (FC) region.…”
Section: Introductionmentioning
confidence: 99%